2002
DOI: 10.1073/pnas.062621699
|View full text |Cite
|
Sign up to set email alerts
|

Naive T cells proliferate strongly in neonatal mice in response to self-peptide/self-MHC complexes

Abstract: Adult naive T cells, which are at rest in normal conditions, proliferate strongly when transferred to lymphopenic hosts. In neonates, the first mature thymocytes to migrate to the periphery reach a compartment devoid of preexisting T cells. We have extensively analyzed the proliferation rate and phenotype of peripheral T cells from normal C57BL͞6 and T cell antigen receptor transgenic mice as a function of age. We show that, like adult naive T cells transferred to lymphopenic mice, neonatal naive T cells proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
118
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 67 publications
9
118
1
Order By: Relevance
“…The lymphopenia observed in NOD mice genetically disposed to develop diabetes is also not comparable with that seen in T cell-deficient hosts (18). During a short time frame in the neonatal phase, T cells seeding the periphery will encounter a severely lymphopenic environment, but the effect of lymphopenia-induced proliferation during this short time period remains unclear and appears minor overall (32,34). Severe induction of lymphopenia may thus be restricted to clinical interventions such as radiation treatment or treatment with cytotoxic drugs that may, in addition to depleting mature peripheral T cells, also affect T cell replenishment by the thymus.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The lymphopenia observed in NOD mice genetically disposed to develop diabetes is also not comparable with that seen in T cell-deficient hosts (18). During a short time frame in the neonatal phase, T cells seeding the periphery will encounter a severely lymphopenic environment, but the effect of lymphopenia-induced proliferation during this short time period remains unclear and appears minor overall (32,34). Severe induction of lymphopenia may thus be restricted to clinical interventions such as radiation treatment or treatment with cytotoxic drugs that may, in addition to depleting mature peripheral T cells, also affect T cell replenishment by the thymus.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, irradiated wild-type hosts may present higher amounts of commensal bacterial Ags due to irradiation-induced gut damage as well as the release of multiple cytokines that may influence lymphopenia-induced proliferation of adoptively transferred naive T cells (25). Second, in contrast to experimental models with genetically lymphopenic or irradiated hosts, the physiological occurrence of lymphopenia throughout an individual's lifetime due to viral infection (26 -28), therapy-related toxicity (29 -31), or age-related changes (neonatal conditions (32)(33)(34) and aging) rarely results in the depletion of all peripheral T cells. However, the incidence of lymphopenia-induced proliferation and homeostasis of peripheral T cell pools under conditions of partial and transient lymphopenia have not been studied in detail.…”
mentioning
confidence: 99%
“…This is evident in the thymus of these mice which contain ϳ15% of SP CD8 cells seen in B6 mice. It has been noted that SP cells in neonatal mice proliferate strongly and display a CD44 high phenotype, reflecting the lymphopenic environment that they are exposed to (25,26). We have compared the phenotype of splenic SP CD8 T cells in B6 and B6.K bϪ D bϪ animals and observed that on day 1 both strains contained a predominance of cells that are CD44 high CD62L low .…”
Section: Discussionmentioning
confidence: 99%
“…An additional situation in which homeostatic proliferation may be part of normal physiology is during ontogeny, when the first waves of thymusderived T cells begin populating secondary lymphoid organs. Indeed, a recent study using bone marrow and thymic-graft models showed that early thymic emigrants expressing ␣␤ TCR proliferate in neonatal mice in a way regulated by the interaction with selfpeptide/MHC and by the size of the peripheral T cell pool (38). Our study suggests that ␥␦ T cells, known to be among the first to be produced early in life, are also likely to proliferate in the T cell-devoid periphery of neonates, and identifies IL-7 and IL-15 as possible modulators of such expansion.…”
Section: Discussionmentioning
confidence: 99%